Korelasi Penilaian Asma Terkontrol Pada Penderita Asma Persisten Sesudah Pemberian Kortikosteroid Inhalasi dengan Menggunakan Asthma Control Scoring System dan Asthma Control Test - Widysanto, Allen; Surjanto, Eddy; Suradi, .; Yunus, Faisal (Jurnal Kedokteran Indonesia, 2009)
Background: The individual parameters to define asthma severity and asthma control overlap significantly. Validated measures, such as ACT, ACS, ACQ, for assessing asthma control are now available, but no comparison among the existing measures has been performed. This study aimed to assess the correlation between ACT and ACS either before of after inhaled corticosteroid ( ICS ).Methods: This was a cohort study. Samples were collected by consecutive sampling. Two asthma control questionnaires, ACS and ACT, must be filled-up by the patients. Spirometry was performed after asthma control questionnaires were completely filled-up. The certain dose of inhaled corticosteroid (ICS ) was given for 2 months, and patients have to repeat the same procedure as they have done after 2 months inhaled corticosteroid administered.Results: The correlation of ACS score based on ACT category score before ICS showed no agreement. In contrary, the correlation of ACS score based on ACT category score after ICS showed significantly moderate agreementConclusion: There was a moderate correlation statistically significant agreement between ACS and ACT assessment when ACS score of 60% was used as the cut off point. Jurnal Kedokteran Indonesia: 1 (1): 56-63Keywords: asthma, persistent, ACS, ACT